Botulinum toxin injection combined with traditional swallowing rehabilitation improved cricopharyngeal dysfunction in neuromyelitis optica spectrum disorder: A case report - He, Zitong; Zhao, Fei; Shan, Yilong; Dou, Zulin; Wen, Hongmei (Frontiers in Neurology, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune diseases of the central nervous system, and often influence optic nerve and medulla oblongata. Previous studies found out that brain abnormalities were not rare in these patients. Medulla oblongata (MO) was commonly involved and usually located at dorsal part. Patients who diagnosed NMOSD with MO lesions were more likely to have dysphagia. Previous reports indicated that the symptoms and signs of NMOSD patients could be controlled after immunosuppressive therapy. This patient was a 49-year-old Asian woman presented with recurrent vomiting and diagnosed NMOSD with MO involvement. However, after immunotherapy in other hospital, she still suffered from dysphagia. She then came to our department and completed videofluoroscopic swallowing study (VFSS) and high-resolution pharyngeal manometry (HRPM). Her UES was not opening with aspiration and the UES residue pressure was higher than normal range, we figured that she had cricopharyngeal (CP) dysfunction. Then the SLP gave her traditional treatment, including catheter balloon dilation. But she failed improvement after treatment for 2 weeks. Then the clinicians decided to inject botulinum toxin (BTX) into her CP muscles, which needed specific location and appropriate dosage. Her UES residue pressure decreased after three times BTX injection. During this time, her SLP adjusted the treatment strategies based on her VFSS and HRM results. Combined BTX injection with traditional treatment, she can now eat food orally without restrictions. This case report we presented can provide treatment strategies for similar patients with dysphagia.